الشراكة الإستراتيجية وأثرها في مواجهة التحدّيات الأمنيَة في ظل العولمة الثقافية: دراسة تطبيقيّة على شرطة أبوظبي - خالد عمر أحمد الزبيدي
This study aims to identify the impact of the strategic partnership strategy in facing security challenges in light of cultural globalization. It also aimed to identify the impact of community, knowledge, and resource partnerships in facing security challenges. The study relied on descriptive analysis and a quantitative approach. The study population consisted of all employees of the Abu Dhabi Police Command Center and its affiliated branches, as well as coordinators of partners from government and private institutions who have a partnership relationship with Abu Dhabi Police. A stratified random sample was taken; in other words, the study population was heterogeneous, numbering 13 ministries (including 100,705 employees), 19 institutions forming bodies, and 27 institutions forming councils and departments. In this study, AMOS were used to analyze the data. However, the study concluded several results, the most important of which are that the increase in the level of strategic partnership will lead to an increase in efficiency in facing security challenges and that the increase in the level of knowledge, community, and resource partnership has a positive impact on increasing the level of facing security challenges. The strategic partnership also positively affects the ability to face security challenges. It was found that there is a mediating role of globalization between strategic and societal partnerships and security challenges, and it has no effect between knowledge partnerships and security challenges. However, this study showed that the Abu Dhabi Police Command Foundation and relevant authorities should enhance the use of the strategic partnership strategy as a main tool in confronting security challenges and strengthen these partnerships with government and private institutions. Through the study’s recommendations, it can contribute to enhancing the ability to confront security challenges considering cultural globalization and enhancing cooperation and partnerships between the various security stakeholders at the Abu Dhabi Police Command Center and partner organizations.